Results of an experiment in a Zion-like geometry to investigate the effect of water on the containment basement floor on direct containment heating (DCH) in the Surtsey Test Facility: The IET-4 test - Allen, M. D.; Blanchat, T. K.; Pilch, M.; Nichols, R. T. (Sandia National Laboratories, 1992)
This document discusses the fourth experiment of the Integral Effects Test (IET-4) series which was conducted to investigate the effects of high pressure melt ejection on direct containment heating. Scale models (1:10) of the Zion reactor pressure vessel (RPV), cavity, instrument tunnel, and subcompartment structures were constructed in the Surtsey Test Facility at Sandia National Laboratories. The RPV was modeled with a melt generator that consisted of a steel pressure barrier, a cast MgO crucible, and a thin steel inner liner. The melt generator/crucible had a hemispherical bottom head containing a graphite limitor plate with a 3.5-cm exit hole to simulate the ablated hole in the RPV bottom head that would be tonned by tube ejection in a severe nuclear power plant accident. The reactor cavity model contained 3.48 kg of water with a depth of 0.9 cm that corresponded to condensate levels in the Zion plant. A 43-kg initial charge of iron oxide/aluminum/chromium thermite was used to simulate corium debris on the bottom head of the RPV. Molten thermite was ejected into the scaled reactor cavity by 6.7 MPa steam. IET-4 replicated the third experiment in the IET series (IET-3), except the Surtsey vessel contained slightly more preexisting oxygen (9.6 mol.% vs. 9.0 mol.%), and water was placed on the basement floor inside the crane wall. The cavity pressure measurements showed that a small steam explosion occurred in the cavity at about the same time as the steam explosion in IET-1. The oxygen in the Surtsey vessel in IET-4 resulted in a vigorous hydrogen bum, which caused a significant increase in the peak pressure, 262 kPa compared to 98 kPa in the IET-1 test. EET-3, with similar pre-existing oxygen concentrations, also had a large peak pressure of 246 kPa.